Multiaxial fatigue and fracture - Macha, Ewald; Bedkowski, W.; Lagoda, T. (Elsevier, 1999)
This volume contains 18 papers selected from 90 presented at the Fifth International Conference on Biaxial/Multiaxial Fatigue and Fracture held in Cracow, Poland 8-12 September 1997. The papers in this book deal with theoretical, computational and experimental aspects of the multiaxial fatigue and fracture of engineering materials and structures. The papers are divided into the following four categories: 1. Proportional cyclic loading 2. Non-proportional cyclic loading 3. Variable amplitude and random loading 4. Crack growth Most papers in this publication talk about the behaviour of constructional materials and elements of machines under non-proportional loading and under variable amplitude and random loading, which are more realistic load histories met in industrial practice. Variable amplitude loading under cyclic load with basic frequency and random loading under load with a continuous band of frequency is classified here. This book gives a review of the latest world success and directions of investigations on multiaxial fatigue and fracture. More and more often publications are results of the co-operation of researchers from different laboratories and countries. Seven out of eighteen papers included here were worked out by international authors teams. This is a symptom of the times, when science and investigations know no borders.